The Lifeworld of Women Domestic Workers: Some Case Studies - Katara, Aditi; Sharma, Pragya (Integrated Journal for Research in Arts and Humanities, 2022)
In the informal sector of metropolitan India, the participation of women domestic workers is steadily increasing. Women participate in domestic work to protect family interests and solve economic crises. Employers compel maximum work from domestic workers with the bare minimum of hospitality. If we consider domestic work on a global scale, it is a solution to the problem of women in the economic system. Domestic work is unorganized, unrewarding, and unrecognized for domestic workers. Women are migrating to domestic work in greater numbers every day, but there is a crucial need to consider their living conditions. Normally, most of the migrant population lives in slums. Migrants in domestic work and women are now a predominant research area for social sciences. This research aims to examine the lifeworld of women domestic workers.